A transmon quantum annealer: decomposing many-body Ising constraints into pair interactions. (16th December 2016) - Leib, Martin; Zoller, Peter; Lechner, Wolfgang
Abstract: Adiabatic quantum computing is an analogue quantum computing scheme with various applications in solving optimisation problems. In the parity picture of quantum optimization, the problem is encoded in local fields that act on qubits that are connected via local four-body terms We present an implementation of a parity annealer with Transmon qubits with a specifically tailored Ising interaction from Josephson ring modulators.